Patient experience after lower extremity amputation for sarcoma in England: a national survey. Issue 12 (5th June 2017) - Furtado, Sherron; Briggs, Tim; Fulton, Jennifer; Russell, Lin; Grimer, Rob; Wren, Vicky; Cool, Paul; Grant, Kristin; Gerrand, Craig
Abstract: Purpose: After amputation, rehabilitation and limb fitting services are critically important to optimise outcomes. We investigated the reported patient experience and variation in limb fitting services after amputation for musculoskeletal tumours in England. Methods: A postal survey instrument was developed following literature review, patient and clinician consultation and piloting. The survey was sent from each of the five bone tumour surgical centres in England. Results: One hundred and five responses were received from 250 patients (42%). The number of limb fitting centres accessed by each surgical centre varied from 2 to 28. Many patients reported care falling short of national standards in areas including pre-amputation counselling, information provision, meeting someone with a similar amputation before surgery, psychological support and falls management. Patients were seen sooner where limb fitting services were on site. Many patients rely on being driven, ambulance and public transport to access services. Conclusion: This study demonstrates variation in the reported experience of limb fitting services by sarcoma patients. Areas for improvement include information provision, pre-amputation counselling, psychological support and falls management. Clinicians should be aware services are highly variable, and this may impact on outcomes. Patients treated in sarcoma centres with limb fitting services on site may experience better care. Implications for Rehabilitation: Rehabilitation services should strive to meet agreed national standards consistently. Where preamputation counselling involving meeting someone with a similar amputation is not possible, good information including video could be helpful. Services should support rehabilitation in the form of early walking aids and efficient prosthetic repair and maintenance. Psychological support, occupational therapy and physiotherapy support must be provided in the acute and chronic phases, including access to long-term rehabilitation care. Rehabilitation programmes must include training to patients and families on reporting, prevention and management of falls. On site services may support better care. Mechanisms for delivering expert specialist care close to home are needed.